The Emerald handbook of crime, justice and sustainable development - Blaustein, Jarrett; Fitz-Gibbon, Kate (Lecturer in criminology); Pino, Nathan; White, R. D. 1956- (Emerald Publishing Limited, 2020)
The Emerald Handbook of Crime, Justice and Sustainable Development brings together a diverse and international collection of essays to critically examine issues relating to crime and justice in the United Nations 2030 Agenda for Sustainable Development. The United Nations 2030 Agenda for Sustainable Development provides an important global framework for advancing human rights, social justice and environmental sustainability. A number of the Agenda's Sustainable Development Goals (SDGs) address issues relating to crime, justice and security, and implicit in the 2030 Agenda is the assumption that members of the international community 'including traditional development actors and the myriad international, non-governmental, private, state and local organizations and actors that collectively contribute to the global governance of crime' must work together to enhance the capacities of both developing and developed countries to achieve this vision. Against this backdrop, this volume analyses and interrogates the SDGs from different theoretical and ideological standpoints originating from within and beyond criminology, illustrating the complex and politically contentious nature of these issues and providing insight into the different possibilities that exist for realising the SDGs and mitigating the risk that initiatives meant to realise the SDGs, may in fact contribute to harmful and counterproductive policies and practices. This book will be essential reading for scholars and students within criminology, criminal justice, socio-legal studies, international relations and development studies.